PEMANFAATAN KITOSAN DARI LIMBAH KULIT UDANG WINDU (Penaeus monodon) SEBAGAI BAHAN ANTIMIKROBA PADA PROSES PENYIMPANAN IKAN NILA (Oreochromis niloticus) - Alifah, Kaviani Suciana; , M.Si., Khabibi; Widodo, M.Si., Didik Setiyo (Chem Info Journal, 2013)
Abstract: Has done research on use of chitosan from shrimp skin (Peneaus monodon) waste as antimicrobial agents in the process of tilapia (Oreochromis niloticus) storage. The purpose of this research is to isolate chitin from the shrimp skin (Peneaus monodon) waste into chitosan, and use as an alternative to be a natural antimicrobial compounds as well as determine the optimum concentration of chitosan solution as a preservative of tilapia (Oreochromis niloticus). This research was carried out by preparation of chitosan from shrimp skin (Peneaus monodon) was begin with deproteination using 3.5% NaOH, demineralization using HCl 1N, and deacetylation using 50% NaOH, analyzing its deacetylation degree by baseline method. Then it was used as an antimicrobial of tilapia, tilapia was immersed in a solution of chitosan by varying the concentration (w/v) 1%, 1.5% and 2% in 2% acetic acid. Storage was varied within 0 days, 1 day, 2 days; 3 days, and 4 days. The results of extraction was found white-grayish colour chitin and white chitosan with deacetylation degree of 66.73%. The optimum concentration of chitosan as an antimicrobial agent of tilapia is 2% with storage time of four day which preserve the fish is consumable.